Power dynamics and policy actions in the changing landscape of local school governance - Carl-Henrik Adolfsson; Daniel Alvunger (Taylor & Francis Group, 2020)
In this paper, we theorize on local school governance through a multi-method case study of a large-sized Swedish municipality by drawing on neo-institutional theory. In light of a changing governing landscape in Sweden in terms of a 're-centralization', new conditions between the state, the local education authorities (LEA) and the schools have emerged. The aim of this study is to examine what policy actions the LEA employ for governing the school and in what ways that principals respond and handle these policy actions. The results point to the fact that the LEA uses a bench-marking strategy through its quality assurance system and intervene if results are poor. Principals seek support from the LEA, but are anxious that their autonomy will be diminished and therefore function as 'gate-. The system for quality assurance is appreciated by principals, but standards aimed at framing discursive communication on quality are criticized. Principals turn to managers below the superintendent, which creates a tension between managers. The study shows that different levels and actors must be taken into account in order to achieve a comprehensive understanding of the multi-layered field of local policy enactment.